Embracing Diversity: Islamic Education through the Multicultural Lens of the Quran (Program Studi Pendidikan Agama Islam, 2023)
This research aims to explore Islamic education from the Quranic perspective in the context of multiculturalism. The primary issue addressed is integrating Quranic values such as tolerance, brotherhood, and justice into an inclusive and relevant Islamic education in today's globalized era. The research method employed is library research, with the primary sources being the Quran and relevant tafsir, along with secondary literature from books, journals, and related materials. The findings reveal that the Quranic perspective provides a strong foundation for multicultural Islamic education by emphasizing the importance of tolerance, brotherhood, and justice. These values can be implemented through the integration of multicultural concepts into the curriculum, the development of inclusive teaching strategies, teacher training, and community participation in the education process. This research contributes to the development of educational strategies that support diversity, creating a fairer and more peaceful society. The significance of this research lies in its potential to shape a more relevant and adaptive Islamic education system amidst the complexities of a diverse global society.